Socialization of the Importance of Maintaining Dental Health and Washing Hands Before Eating in Children at Subang Mewah Sanggar Guidance (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Dental and hand hygiene are two important aspects of maintaining children's overall health. However, children's awareness and knowledge about dental care and washing hands before eating are still relatively low, especially in non-formal educational environments such as Sanggar Bimbingan. This Community Service Activity (PKM) aims to enhance the understanding and healthy behaviors of children at Sanggar Bimbingan Subang Mewah through interactive and educational outreach. The methods used include lectures, discussions, question and answer sessions, and practical demonstrations, as well as the distribution of toothbrushes and toothpaste. The results of the activity showed an increase in children's knowledge and enthusiasm in adopting the habit of brushing their teeth regularly and washing their hands before eating. With this program, it is hoped that healthy habits will be formed from an early age, which can contribute to the quality of life of children in the future.